Temperature and moisture effects on the N-mineralization of a poultry manure amended soil - Llorca, R.=700 1 Dendooven, L.
(Es, En)
ilus., 23 ref.
Keywords: TEMPERATURA DEL SUELO; CONTENIDO DE AGUA EN EL SUELO; MINERALIZACION; NITROGENO; ABONOS ORGANICOS; ESPAÑA; GALLINAZA